Cubichnia and Praedichnia in fossil ichnites of a flat fish from the Lower Cretaceous Talmest palaeoichnological site, Western High Atlas (Morocco). Issue 1 (4th November 2020) - Lkebir, Noura; Masrour, Moussa; Torices, Angélica; Pérez-Lorente, Félix
Abstract: During a study of the Talmest ichnological site (2011–2012), where theropod and sauropod tracks were discovered, other ichnites were found that are analyzed in the present work. There are two basic types attributed to two different activities produced by the same vertebrate at the bottom of a flooded area. One type ( Cubichnia ) is produced by sliding on the bottom surface while the other ( Praedichnia ) is the result of the excavation, removal and accumulation of mud from the upper levels of the sediment. The analysis of structures and possible trace makers leads to the conclusion that the ichnites were produced by a freshwater fish, during its resting activity on the bottom and during the search for food.